2015
DOI: 10.3109/13880209.2015.1014920
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and biological activities ofAlbizia myriophyllawood

Abstract: Context: Albizia myriophylla Benth (Leguminosae) is a medicinal plant widely used in Thailand and other Asian countries as a folk medicine remedy for many ailments. Objective: The objective of this study is to investigate the chemical compositions, antibacterial activity, and cytotoxicity of A. myriophylla wood. Materials and methods: The structure identification of the isolated compounds was established using spectroscopic methods. In vitro antibacterial activity against Streptococcus mutans, Staphylococcus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…MS and NMR data (table 2) of 5 were compatible with those of published ones. [2,12] The dextrorotatory value of 5 {[α] D 25 +38.9 (c 4.25, MeOH)} matched with the one of [α] D 20 +48.5 (c 0.8, acetone-H2O) reported for (2S,3S,4S)-7,3,4-trihydroxy-2,3-cisflavan-3,4-cis-diol. [13] Therefore 5 was assigned as (2S,3S,4S)-7,3,4,3',4'-pentahydroxyflavane.…”
Section: Figure 3: Structures Of Isolated Compounds Frommentioning
confidence: 54%
See 2 more Smart Citations
“…MS and NMR data (table 2) of 5 were compatible with those of published ones. [2,12] The dextrorotatory value of 5 {[α] D 25 +38.9 (c 4.25, MeOH)} matched with the one of [α] D 20 +48.5 (c 0.8, acetone-H2O) reported for (2S,3S,4S)-7,3,4-trihydroxy-2,3-cisflavan-3,4-cis-diol. [13] Therefore 5 was assigned as (2S,3S,4S)-7,3,4,3',4'-pentahydroxyflavane.…”
Section: Figure 3: Structures Of Isolated Compounds Frommentioning
confidence: 54%
“…[1] In Vietnamese traditional medicine, it was used to cure cough, bronchitis, toothache, obesity, dyspepsia, diabetes, cancer etc. [1][2][3] There were many researches about chemical constituents and bioactivities of Albizia myriophylla. [2][3][4][5] However, in Vietnam, there has been no chemical study on this plant although it is now cultivated at Phu Yen province for the internal commercial use thanks to its above-mentioned medicinal value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibacterial activities of lupinifolin against a variety of pathogens have also been documented by several groups of investigators. Joycharat and colleagues [5] reported that lupinifolin extracted from A. myriophylla wood exhibited a strong antibacterial action against Streptococcus mutans using a broth microdilution method. A separate study by this group of researchers using a violet staining method showed antibiofilm-producing activity of lupinifolin against multidrug-resistant enterococci [10].…”
Section: Development Of Lipid-based Nanocarriers For Increasing Gastrmentioning
confidence: 99%
“…Several Albizia species organ extracts from different countries had been reported displaying antimicrobial properties. They include the extracts of A. zygia leaf [4], A. julibrissin leaf, stem and flower [5], A. amara leaf, flower, pod and bark [6], A. lebbeck seed [7], A. anthelmintica root bark [8], A. amara and A. saman leaves [9], wood [10], A. andianthifolia bark and root [11]. Seed extracts from some endemic Albizia of Madagascar also exhibited antimicrobial effects [12].…”
Section: Introductionmentioning
confidence: 99%